Math and science for young children - Howard, Rebecca; Charlesworth, Rosalind (Mason Cengage, 2025)
"Math and Science for Young Children, Eighth Edition, is designed to be used by students in training and by teachers in service in early childhood education. To the student, it introduces the excitement and extensiveness of math and science experiences in programs for young children. For teachers in the field, it presents an organized, sequential approach to creating a developmentally appropriate math and science curriculum for preschool and primary school children"--
Previous editions entered under the first author, Rosalind Charlesworth.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Primary).; Science -- Study and teaching (Primary).